Comparison of fatty acid profiles of dried and raw by‐products from cultured and wild fishes. Issue 9 (5th April 2017) - Rincón‐Cervera, Miguel Ángel; Villarreal‐Rubio, María Beatriz; Valenzuela, Rodrigo; Valenzuela, Alfonso
Abstract : Fish by‐products may become alternative sources of eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA). However, due to the high enzymatic activity in these biological tissues, special care must be taken to prevent lipid oxidation and hydrolysis. In this work, several by‐products from Chilean fishes (farmed salmon and wild red cusk‐eel and yellowtail kingfish) were dried at 105°C for 3 h to remove water and inactivate enzymes. The effect of temperature on EPA and DHA levels was assessed by comparing fatty acid profiles of raw and dried by‐products. Drying at 105°C for 3 h was considered an adequate process to obtain dried powders from fish by‐products with appreciable amounts of EPA and DHA, even though EPA and DHA values showed a certain decrease after drying. Several methodologies involving food‐grade solvents were checked to evaluate their suitability for lipid extraction from dried by‐products, being Soxhlet extraction with n‐hexane identified as the most suitable process in terms of extraction yield and EPA/DHA values. Cholesterol amount was also studied, being the highest and lowest amounts found in liver and viscera from farmed salmon, respectively. Practical applications: In fish processing plants, raw by‐products are collected after fish evisceration, and they can be transported to oil extraction facilities, although their lipids may be easily degraded unless special precautions are taken to preserve such biomass. Raw fish by‐products must be subjected to water removal and enzyme inactivation to prevent lipid degradation and hydrolysis, and it is desirable that such actions are carried out in the processing plants themselves to ensure the maximum oil quality. Drying at 105°C for a short time (3 h) was assayed in this work because of its simplicity, low cost, scalability, and feasibility to be installed in fish processing plants. Soxhlet procedure with n‐hexane is effective to extract lipids containing EPA and DHA from dried by‐products for nutritional or nutraceutical purposes. Because of water removal, lipid extraction efficiency from dried by‐products is enhanced and less solvent is needed, which is economically and environmentally desirable. Raw by‐products from cultured and wild fishes are dried at 105°C for 3 h and fatty acid profiles are compared between raw and dried by‐products to assess the potential decreasing effect of temperature on the levels of polyunsaturated fatty acids, especially EPA and DHA. Different lipid extractions using solvents are also compared to check their influence on fatty acid profiles. Additionally, cholesterol amount is quantified in the lipid fraction extracted from dried fish by‐products. Abstract : Raw by‐products from cultured and wild fishes are dried at 105°C for 3 h and fatty acid profiles are compared between raw and dried by‐products to assess the potential decreasing effect of temperature on the levels of polyunsaturated fatty acids, especially EPA and DHA. Different lipid extractions using solvents are also compared to check their influence on fatty acid profiles. Additionally, cholesterol amount is quantified in the lipid fraction extracted from dried fish by‐products.